Intrapartum Amnioinfusion for Recurrent Variable Decelerations and Neonatal Morbidity: A Systematic Review and Meta-Analysis - Brock E. Polnaszek; Julia Rossen; Katherine H. Bligard; Angela Hardi; Emily S. Miller; Methodius G. Tuuli; Adam K. Lewkowitz (IMR Press, 2024)
Background: The objective was to estimate the effect of intrapartum amnioinfusion (AI) for recurrent variable decelerations on neonatal morbidity. The primary outcome was composite neonatal neurologic morbidity assembled from individual neonatal outcomes used clinically with suspected hypoxic-ischemic encephalopathy (HIE). Secondary outcomes were composite neonatal morbidity not associated with HIE. Methods: Data Sources: A predefined, systematic search was conducted through Ovid Medline, Embase, CINAHL PLUS, Cochrane library (including CENTRAL), Scopus, and Clinicaltrials.gov and was used to identify studies assessing the relationship between intrapartum AI and neonatal morbidity yielding 345 unique citations from 1982 to 2018. Study Eligibility Criteria: Randomized control trials that compared intrapartum AI to no AI for recurrent variable decelerations and included neonatal outcomes were included. Randomized trials comparing AI for other indications (e.g., meconium aspiration syndrome) were excluded, as were studies on intrapartum AI that lacked a control group (i.e., no amnioinfusion). Results: A total of 3 randomized control trials met the selection criteria. Outcomes from 282 neonates exposed to intrapartum AI for recurrent variable decelerations were compared to those from 286 who had fetal monitoring with recurrent variable decelerations but did not receive AI. There were no data on neonatal neurologic morbidity outcomes related to HIE. Among the data available, composite neonatal morbidity was not significantly different with AI (28.7% vs. 59.1%, pooled risk ratio, -0.30; 95% CI (95% confidence interval) -0.99-0.40; I2 = 94.51%; p = 0.40). Separated by individual outcomes contributing to the composite, intensive care unit admissions (ICU) (1 study; 6.8% vs. 16.5%; risk ratio 0.45; 95% CI 0.25-0.83) were less likely in those receiving an intrapartum AI, compared to no intrapartum AI while there was no difference in umbilical cord pH <7.20 (1 study; 19% vs. 8%; p = 0.62). There was no difference in Apgar scores <7 at 1 and 5 minutes on pooled analysis. Conclusions: Few studies have been published on the effect of intrapartum AI for recurrent variable decelerations on neonatal morbidity. Nevertheless, this meta-analysis suggests that intrapartum AI for recurrent variable decelerations may improve surrogate markers of neonatal morbidity, but further research is warranted.